Unmet Needs of People With Parkinson's Disease and Their Caregivers During COVID-19-Related Confinement: An Explorative Secondary Data Analysis - Hanff, Anne-Marie; Pauly, Claire; Pauly, Laure; Schröder, Valerie E.; Hansen, Maxime; Meyers, Guilherme Ramos; Kaysen, Anne; Hansen, Linda; Wauters, Femke; Krüger, Rejko (Frontiers in Neurology, 2021)
Self-perceived unmet needs in people with typical and atypical parkinsonism (PwP) and their caregivers, support network, personalized ways to address self-perceived unmet needs during confinement, as well as the prevalence of self-reported COVID-19 related symptoms, confirmed SARS-CoV-2 infection, and self-reported COVID-19 related hospitalization in Luxembourg and the Greater Region were assessed. From 18th March to 10th April 2020, 679 PwP were contacted by phone. Data was collected in the form of a semi-structured interview. The thematic synthesis identified 25 themes where PwP need to be supported in order to cope with consequences of the pandemic, and to adapt their daily and health-related activities. The present work highlights that in the context of personalized medicine, depending on the individual needs of support of the patient the identified self-perceived unmet needs were addressed in various ways ranging from one-directed information over interaction up to proactive counseling and monitoring. Family and health professionals, but also other support systems were taking care of the unmet needs of PwP (e.g. shopping, picking-up medication, etc.) during the pandemic. 7/606 PwP (1.15%) reported COVID-19 related symptoms, 4/606 (0.66%) underwent a rRT-PCR-based diagnostic test and 2/606 (0.33%) were confirmed as SARS-CoV-2 positive. None of these PwP reported being hospitalized due to COVID-19. Our results will allow health professionals to expand their services in a meaningful way i.e. personalize their support in the identified themes and thus improve the healthcare of PwP in times of crisis.